Identifying written translation in criminal proceedings as a separate right: scope and supervision under European law - Brannan, James (The Journal of Specialised Translation, 2017)
Discussion of the right to language assistance in criminal proceedings has tended to focus more on interpretation, neglecting written translation. The European Court of Human Rights has certainly laid down the principle that documents, in particular the indictment, are covered by the relevant provisions of the European Convention on Human Rights (ECHR), but has often found an oral translation or explanation to be sufficient. Directive 2010/64/EU, whilst providing for the translation of essential documents in a specific article and emphasising the importance of quality, reflects to some extent the principles and limitations that already existed under the ECHR. This article will look at the scope of the right to written translation, first under the ECHR and Strasbourg case-law, then under the relevant EU directives, analysing the different types of document that should be translated and situations that may arise. The proper transposition of the EU legislation should strengthen guarantees in the area of written translation, as a separate right — provided the oral alternative remains an exception — ensuring more consistent and effective assistance in criminal proceedings.